Bimbingan Teknis OSS RBA dan LKPM Online Guna Meningkatkan Realisasi Investasi Kota Denpasar - Putra, Adrian Pratama (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Investment is an activity that is very profitable financially, and also an activity that has a high risk. The investment process includes understanding the basics of investment decisions and how to organize activities in the decision-making process. In the investment business world, especially stocks, price information can change quickly depending on the offers that occur on the stock exchange and other aspects that are also very influential. Population growth, industrial development, restaurants and fast food restaurants cause the use of cooking oil to increase. The increase in the use of cooking oil will cause an increase in frying waste. Therefore, as a form of community service from the Bali Nahdlatul Ulama Institute of Science and Technology (ISTNUBA), we try to Applying it to business actors in Denpasar City with the hope of increasing the understanding of business actors regarding the provisions for implementing investment regarding OSS-RBA, Investment Activity Reports (LKPM), and also understanding of policies in terms of investment. The method used is empirical research where by providing direct guidance to business actors. The results through this study indicate that the implementation of OSS-RBA has been carried out and is in an effective level as an effort to accelerate the licensing process in Denpasar City in accordance with the regulatory basis, namely Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing but the "Online Single Submission" System. Remains a system that follows the times and continues to be developed over time to minimize problems related to licensing